Understanding thermal justice and systemic cooling poverty from the margins: intersectional perspectives from Rio de Janeiro - Mazzone, A; De Cian, E; de Paula, E; Ferreira, A; Khosla, R (Taylor and Francis, 2024)
Heatwaves, which are escalating in frequency, duration and intensity, have prompted governments worldwide to issue vital health warnings to protect populations. These include urging individuals to stay cool, hydrated, avoid direct sun exposure and minimise strenuous activities. Regrettably, a significant segment of the population faces substantial challenges in accessing these crucial recommendations due to a range of issues termed “systemic cooling poverty”. Systemic cooling poverty encompasses intricate layers of physical, social and intangible infrastructural deficiencies, impeding the provision of essential services necessary to ensure thermal safety during extreme heat episodes. Through an intersectional mixed-method examination, this study brings empirical evidence of the structural factors that exacerbate inequalities in attaining thermal safety among the African–Brazilian community, LGBTQI+ and disabled, living in two favelas in Rio de Janeiro. By shedding light on these lived experiences of cooling poverty, we contribute to the understanding of targeted interventions and policy measures that can alleviate the impacts of extreme heat and safeguard public health and well-being as temperatures rise.